Abuse of amantadine in poultry may be associated with higher fatality rate of H5N1 infections in humans. Issue 6 (24th February 2022) - Yuan, Shu; Jiang, Si‐Cong; Zhang, Zhong‐Wei; Fu, Yu‐Fan; Zhu, Feng; Li, Zi‐Lin; Hu, Jing
Abstract: Amantadine, an antiviral drug, has been widely used in human anti‐influenza treatments. However, several highly pathogenic avian influenza viruses show amantadine‐resistance mutations in the viral matrix 2 (M2) protein. Here we analyzed global H5N1 sequencing data and calculate possible correlations between frequencies of key mutations in M2 and the mortality rates. We found that the frequency of L26I/V27A mutation in M2 (isolated from both human and avian hosts) is linearly correlated with the mortality rates of human H5N1 infections. The significant correlation between M2 mutations in avians and the mortality rates in humans suggests that the pre‐existence of L26I/V27A in birds may determine patient fatalities after transinfections from avian to human hosts. 100% prevalence of L26I/V27A mutation increased the mortality rates from 51% (95% confidence interval [CI] 37%–65%) to 89% (95% CI 88%–90%). Mutations involving Leu26 or Val27 were identified to be the major mutations emerging from drug selection pressure. Thus the emergence of the super H5N1 virus with a fatality of over 90% may be attributed to the abuse of amantadine in poultry, especially in some southeast Asian countries. A more stringent control to antiviral veterinary drugs is imperative. Highlights: Highly pathogenic H5N1 viruses show amantadine‐resistance mutations in M2 protein. The frequency of L26I/V27A mutation in M2 is linearly correlated with mortality rates. Pre‐existence of L26I/V27A in birds may determine the fatalities in humans. Frequencies of mutations in PB2 and NA were not correlated with the mortality rate. The H5N1 virus with a fatality of over 90% may be attributed to the abuse of amantadine in poultry.